Upaya Meningkatkan Pemahaman Siswa Untuk Mencegah Perilaku Cyberbullying Melalui Layanan Informasi Teknik Modeling Simbolik Di SMP Negeri 4 Kerinci - Rifal Nawaldi; Hengki Yandri; Harmalis Harmalis; Dosi Juliawati (Institut Agama Islam Negeri Kerinci, Indonesia, 2022)
This study aims to improve students' understanding of preventing cyberbullying through the Information Service of Symbolic Modeling Techniques. This research is a pre-experimental type with a one-group pretest-posttest design. The total sample was 47 students from Class VIII of Junior High School 4 Kerinci. The data is revealed using a scale of understanding cyberbullying that has been tested for validity and reliability. The data that has been collected is analyzed using the Paired sample T-test. The results showed that students' understanding of Cyberbullying behaviour before being given Symbolic Modeling Technique Information services was in low category (34%). Then after being given the Symbolic Modeling Technique Information Service, students' understanding of Cyberbullying behaviour increased by a very high category (62%). Furthermore, the results of data analysis using the Paired sample T-test showed the sig value. (2-tailed) = 0.000 < α = 0.05, then H0 is rejected, and Ha is accepted, so it can be interpreted that there is a difference in the average score of understanding cyberbullying students before and after treatment in the form of Symbolic Modeling Technical Information Services. Thus, it is proven that the Information Service of Symbolic Modeling Techniques can improve students' understanding of the dangers of Cyberbullying behaviour.